Remote Sensing Techniques for Identifying Flood Prone Areas Using the Vegetation Index, Water Index, and Simple Additive Weighting Methods for Mekarsari Areas, Cianjur Regency, West Java - Harnani Harnani; Putri Savira (Journal of Earth and Marine Technology (JEMT), 2023)
Flood is a natural disaster with an intensity that often occurs in cities on a scale with excess water discharge in some areas. This research was conducted to determine the risk of flooding in Mekarsari Village and its surroundings, Cianjur Regency, West Java. (According to InaRisk, 2022) Risk and danger of flooding Moderate – High. This study uses data for the entire year 2022. With several parameters used in this study including land cover, rainfall, soil type, slope, NDVI, NDWI and SAVI. Simple Additive Weighting or weighting for each parameter with different results, according to the classification of each of these parameters. The results of this weighting will become a Flood Hazard Risk Map which was previously the result of overlay and intersection of land cover map, rainfall map, soil type map, slope map, Normalized Difference Vegetation Index map, Normalized Difference Water Index map and Soil Adjusted Vegetation Index map. On the Flood Disaster Risk Map there are five categories of vulnerability levels Not Hazardous, Less Hazardous, Moderate, Hazardous and Very Hazardous. The cause of the risk of flooding in the study area is that most of the land use is diverted to rice fields, plantations, dry agricultural land and settlements so that the lack of vacant land causes low absorption of rainwater and also steep slopes and high elevations which also cause rainwater to be stored in the lowlands. settlements) with moderate to high rainfall intensity every month. There is also a lack of education for the community to mitigate the risk of flood disasters so that waste management and waterways in settlements are inadequate and well managed.